Examination of the PC-PTSD in previously deployed Air Force Medical Service personnel. Issue 4 (4th July 2018) - Tvaryanas, Anthony P.; Maupin, Genny M.; White, Edward D.; Schroeder, Valarie M.; Mahaney, Heather J.
ABSTRACT: This study assessed the performance of the PC-PTSD in diagnosing postdeployment posttraumatic stress disorder (PTSD) in a cohort of Air Force Medical Services personnel ( N = 18, 530). The prevalence of PTSD in the cohort was 5.18% based on medical record data. The area under the receiver operating characteristic curve was 0.69, indicating poor classification accuracy. Sensitivity was 47.55%, specificity was 90.68%, positive predictive value was 21.79%, and negative predictive value was 96.94%. The positive and negative likelihood ratios were 5.10 and 0.58, respectively. Several risk factors were found to be associated with a diagnosis of postdeployment PTSD: being a nurse, being enlisted in the medical service career field, being enlisted in the mental health service career field, those over age 30, being a member of the Active Duty service component, and having one's first deployment be to Iraq. Being an officer was found to be a protective characteristic. These factors could potentially improve screening for PTSD among Air Force healthcare personnel.